Application of structured inquiry learning models to enhance students' critical thinking skills - Riska Muzayanah; Tutut Nurita (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
This study aimed to describe the implementation of learning, the improvement of students' critical thinking skills, and the student responses after applying the structured inquiry learning model to the sub-material of fluid pressure. This type of research used a pre-experimental design with one group pretest-posttest design. The research subjects used were students of the public junior high schools in Surabaya, Indonesia. This study used several instruments in the form of learning implementation observation sheets, test sheets, and questionnaire sheets which were then analyzed by quantitative description. The results showed that the implementation of learning obtained very good criteria with mode 4. Normality tests, paired t-tests, and N-Gain were used to analyze research data. The result of the standard test is significant. The value is 0.122, which means the data is normally distributed. Paired t-test produces a Sig value of 0.000 <0.05, which means a significant difference after being given treatment in a structured inquiry learning model. The improvement of students' critical thinking skills can also be seen from the N-Gain results on each critical thinking skill indicator with a score of 0.81 (high), 0.77 (high), 0.91 (high), 0.76 (high). and 0.84 (high). Students gave positive responses to the application of this learning model with an average score of 93.81%, and the criteria were very high. These results indicate that students' critical thinking skills can improve after the applied structured inquiry learning model.